Assessment of solar photocatalytic degradation and mineralization of amoxicillin trihydrate (AMT) using slurry and fixed-bed batch reactor: efficacy of parabolic trough collector. Issue 42 (12th April 2016) - Dixit, Divya; Verma, Anoop; Gupta, Saurabh; Bansal, Palak
Abstract : Heterogeneous photocatalytic mineralization of amoxicillin trihydrate (AMT) using TiO2 in suspended and supported form has been investigated in the present study. Abstract : Heterogeneous photocatalytic mineralization of amoxicillin trihydrate (AMT) using TiO2 in suspended and supported form has been investigated in the present study. Cement beads and alginate balls were used for the immobilization of TiO2 for the degradation of AMT. The dip coating method was used for catalyst immobilization on the cement beads, whereas the catalyst was physically entrapped in alginate gel. 87%, 69% and 51% degradation was observed under shallow pond slurry reactor, coated cemented beads and immobilized sodium alginate balls, respectively, at optimized conditions. XRD and solid spectra analysis of TiO2 confirmed that no deformities occurred in the structure of catalyst after use. Reduction in COD and TOC along with the generation of ammonium ions further indicates the mineralization of AMT. Experiments conducted on a parabolic trough collector (PTC) with TiO2 immobilized cement beads at a flow rate of 1.0 L min −1 in the presence of oxidant (0.12 g L −1 ) yielded 92% degradation within 4 h of irradiation. The structure of TiO2 was found to be intact after the fifth recycle.